Li diffusion in (110)‐oriented LiCoO2 thin films grown on Au and Pt (110) substrates. (29th July 2016) - Shiraki, Susumu; Oki, Hideki; Hitosugi, Taro
Abstract : We fabricated epitaxial LiCoO2 (110) thin films on the single‐crystal Au(110) and Pt(110) substrates using pulsed laser deposition. We found that the chemical diffusion coefficient of Li ions in the LiCoO2 (110) thin film on the Pt(110) substrate was higher than that observed in the thin film on the Au(110) substrate. We discussed the origin of this difference in the chemical diffusion coefficient in the epitaxial LiCoO2 films. Copyright © 2016 John Wiley & Sons, Ltd.